"[Y]ou are better off talking to a f****** wall": The perceptions and experiences of grievance procedures among incarcerated people in Ireland. Issue 2 (19th May 2022) - van der Valk, Sophie; Aizpurua, Eva; Rogan, Mary
Abstract: The ways in which grievance procedures are used and perceived by incarcerated people raise important questions about the operation of procedural justice and legal consciousness and mobilization scholarship in settings where rights are especially vulnerable. This paper analyzes perceptions and usage of the grievance procedure for incarcerated people using survey data from people ( N  = 508) in three prisons in Ireland. We find that incarcerated people's views of the grievance procedures are generally negative, though some use it, especially those serving long sentences and those in segregation, with education level not significant in terms of usage. Additionally, having confidence in staff is associated with satisfaction with the procedure, as is the perception that one's rights are respected, showing important connections between perceptions of complaints and aspects of legal consciousness. We suggest a need for further situated analyses of procedural justice and legal consciousness, as well as practical requirements for complaints systems to elicit confidence among incarcerated people.